Single-cell RNA sequencing reveals ex vivo signatures of SARS-CoV-2-reactive T cells through ‘reverse phenotyping’ - David S. Fischer (Nature Portfolio, 2021)
High resolution characterisation of the virus specific T cell response to SARS CoV2 provides further understanding to the immune response to the infection. Here the authors apply a reverse phenotyping approach to interrogate the SARS-CoV-2 T cell compartment at single cell resolution.”